PENERAPAN MODEL E-LEARNING DALAM UPAYA MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IX.B SMP NEGERI 1 PAYUNG - ZUHRI AZIS (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2023)
This study aims to determine whether the application of the e-learning model can improve social studies learning outcomes for class IX.B students of SMP Negeri 1 Payung. This is because the teacher has not utilized the existing learning media, the methods used by the teacher is still using conventional methods causing learning outcomes to be unstatisfactory or still below the KKM, which is 76. This classroom action research is designed in two cycle is carried out in four stages, namely: planning, implementation, observation and reflection. This subjects of this study were class IX.B students of SMP Negeri 1 Payung for the academic year 2019/2020 with a total of 33 students consisting of 18 male students and 15 female students. The object of this research is the improvement of social studies learning outcomes. Social studies learning outcomes data were collected using a social studies learning outcomes test, which consisted of 15 multiple choice questions and 3 essay questions. The criteria for the success of the action are if the average student social studies learning outcomes are at least 76 with classical mastery of at least 85%. The result showed that the average social studies learning outcomes from 71,87 in the pre-cycle to 76,95 in the first cycle and 81,58 in the second cycle with classical completeness from 36,36% in the pre-cycle to 64% in the first cycle and 88% in cycle 2. Thus the application of the e-learning model can improve social studies learning outcomes for class IX.B students of SMP Negeri 1 Payung. ABSTRAKPenelitian ini bertujuan untuk memgetahui apakah penerapan model e-learning dapat meningkatkan hasil belajar IPS siswa kelas IX.B SMP Negeri 1 Payung. Hal ini dikarenakan guru belum memanfaatkan media pembelajaran yang ada, metode yang digunakan guru masih menggunakan metode konvensional menyebabkan hasil belajar kurang memuaskan atau masih di bawah KKM yaitu 76. Penelitian tindakan kelas ini dirancang dalam dua siklus. Setiap siklus dilaksanakan dalam empat tahapan yaitu: perencanaan, pelaksanaan, observasi dan refleksi. Subjek penelitian ini adalah siswa kelas IX.B SMP Negeri 1 Payung tahun pelajaran 2019/2020 dengan jumlah 33 siswa terdiri dari 18 siswa laki-laki dan 15 siswa perempuan. Objek penelitian ini adalah peningkatan hasil belajar IPS. Data hasil belajar IPS dikumpulkan dengan menggunakan tes hasil belajar IPS yang berjumlah 15 butir soal pilihan ganda dan 3 soal uraian. Kriteria keberhasilan tindakan jika rata-rata hasil belajar IPS siswa minimal 76 dengan ketuntasan klasikal minimal 85%. Hasil penelitian menunjukkan bahwa rata-rata hasil belajar IPS dari 71,87 pada pra siklus menjadi 76,95 pada siklus I dan 81,58 pada siklus II dengan ketuntasan klasikal dari 36,36 % pada pra siklus menjadi 64% pada siklus I dan 88% pada siklus 2. Dengan demikian penerapan model pembelajaran e-learning dapat meningkatkan hasil belajar IPS siswa kelas IX.B SMP Negeri 1 Payung.